Comparison of the Effectiveness of Schroth Exercise Method and Combined (Manual Therapy + Schroth Exercise Method) Method in Idiopathic Adolescent Scoliosis - Seyyedeh Sahra Karimi; Ömer Şenel (İstanbul Gelişim Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Aim: This study aimed to assess the impact of the Schroth exercise method alone versus a combination of the Schroth exercise method and manual therapy on adolescent idiopathic scoliosis patients.Method: Participants aged 11-18 were divided into two groups: one practicing Schroth exercises and the other combining these exercises with manual therapy. Gibbosity, static and dynamic balance, visual perception, and quality of life were measured at baseline and after 3-month intervention period.Results: Results indicated no significant differences between the groups in gender distribution, age, height, weight, body mass index, static and dynamic balance, gibbosity, and quality of life (p>0.05), except for visual perception, where the combined therapy group showed better results (p<0.05). Despite some observed benefits in gibbosity, quality of life, and static balance in the combined therapy group, these differences were not statistically significant (p>0.05).Conclusion: The study concludes that, except for improved visual perception in the combined therapy group, there were no significant advantages over the Schroth exercise method alone in treating adolescent idiopathic scoliosis.